2007
DOI: 10.1111/j.1469-8137.2007.02206.x
|View full text |Cite
|
Sign up to set email alerts
|

Citrate exudation from white lupin induced by phosphorus deficiency differs from that induced by aluminum

Abstract: Summary• Both phosphorus (P) deficiency and aluminum (Al) toxicity induce root exudation of carboxylates, but the relationship between these two effects is not fully understood. Here, carboxylate exudation induced by Al in Lupinus albus (white lupin) was characterized and compared with that induced by P deficiency.• Aluminum treatments were applied to whole root systems or selected root zones of plants with limited (1 µ M ) or sufficient (50 µ M ) P supply.• Aluminum stimulated citrate efflux after 1-2 h; this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 46 publications
2
47
0
2
Order By: Relevance
“…However, the mechanisms of soil P mobilization by carboxylates especially the relative contributions of ligand exchange, ligand-promoted dissolution of P-bearing minerals such as Fe/Al oxides, complexation of Al, Ca, or Fe and changes in solution P speciation, and carboxylate adsorption promoting changes in surface charges on clays and Al/Fe oxides are not fully understood despite some progress on the physiological control of carboxylate synthesis and excretion. Involvement of anion channels in organic acid excretion is confirmed by the action of anion channel blockers (Neumann et al, 1999;Wang et al, 2007). It is found that the Al-activated malate transporter mediates malate exudation (Hoekenga et al, 2006) and the multidrug and toxic compound extrusion transporter mediates citrate exudation (Magalhaes et al, 2007), and both may confer Al resistance.…”
Section: Mycorrhizal Associationmentioning
confidence: 99%
“…However, the mechanisms of soil P mobilization by carboxylates especially the relative contributions of ligand exchange, ligand-promoted dissolution of P-bearing minerals such as Fe/Al oxides, complexation of Al, Ca, or Fe and changes in solution P speciation, and carboxylate adsorption promoting changes in surface charges on clays and Al/Fe oxides are not fully understood despite some progress on the physiological control of carboxylate synthesis and excretion. Involvement of anion channels in organic acid excretion is confirmed by the action of anion channel blockers (Neumann et al, 1999;Wang et al, 2007). It is found that the Al-activated malate transporter mediates malate exudation (Hoekenga et al, 2006) and the multidrug and toxic compound extrusion transporter mediates citrate exudation (Magalhaes et al, 2007), and both may confer Al resistance.…”
Section: Mycorrhizal Associationmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29] Based on these prior observations we hypothesized that A. thaliana may utilize information regarding nutrient availability to influence decisions regarding competition based on neighbor identity. In other words, nutrient availability may influence the production of specific exudates associated with KR which could alter the RSA accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Nutrient availability also alters exudate production and composition with the potential to impact both interorganismal interactions as well as nutrient uptake. [26][27][28][29] For example, in Sorghum bicolor reduced nitrogen and phosphorus levels promote the release of 5-deoxystrigol which encourages the recruitment of mycorrhizal fungi. 26 Clearly, plants must integrate information regarding both neighbor identity as well as nutrient availability if they are to successfully compete in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…White lupin (Lupinus albus), which forms cluster roots, has become a model plant for the study of P i acquisition due to its exceptional ability to acquire nutrients unavailable to most other plants (Neumann and Martinoia, 2002;Vance et al, 2003;Tian et al, 2009;Zhu et al, 2009;Cheng et al, 2011aCheng et al, , 2011b. Cluster roots increase the root surface area for enhanced P i absorption and exude organic anions (Johnson et al, 1996;Massonneau et al, 2001;Sas et al, 2001;Wang et al, 2007) and acid phosphatases (Gilbert et al, 1999;Miller et al, 2001) that release P i from sparingly soluble inorganic and organic compounds. In addition, highaffinity phosphate TPs help with the acquisition of solubilized P i .…”
mentioning
confidence: 99%